The Role of Islamic Banking and Government Programs in Improving UMKM Performance - Rahmayanti, Dini (UIN Raden Mas Said Surakarta, 2025)
MSMEs contribute a lot to a region's economy, from absorbing labor and leveling the economy to providing foreign exchange for international-scale MSMEs. Therefore, the government pays close attention to MSMEs under the Ministry of Cooperatives and MSMEs. This study aims to analyze the role of Islamic banking and government programs in improving MSME performance by involving 141 respondents who entered Pintar UMKM Salatiga. Using a quantitative approach, data were collected through interviews and questionnaire results filled out by MSME actors in Salatiga City who had received financing from Islamic banking. Data analysis in this study used moderated regression analysis to determine whether the moderating variable can strengthen or weaken the relationship between the independent variable and the dependent variable. The results of this study show that Islamic banking and entrepreneurial competence significantly influence the performance of MSMEs in Salatiga. However, government programs do not significantly affect the performance of MSMEs in Salatiga. Likewise, the entrepreneurial competence variable cannot strengthen the relationship between Islamic banking and government programs on the performance of MSMEs in Salatiga.